Factors affecting online purchasing behaviour among generation Y in Melaka - Jumbri, Isma Addi; Roni, Noor Azura; Zainudin, Mohamad Zahir; Zaini, Muhammad Zaki (Penerbit Universiti Teknikal Malaysia Melaka, 2021)
The growth of the internet and information technology has immensely contributed to online shopping popularity. Generation Y or also known as Gen Y is the age cohort that comprises most online shoppers of many developed and developing countries. Thus, this study aims to analyze Gen Y’s online purchase behaviour in Melaka and identify the drivers of behaviour. The survey was participated by 384 Gen Y respondents. Findings from the study reveal that majority of the respondents spend 3-4 hours browsing online daily, indicating that they are a heavy user of the internet and more receptive to the adoption of technological innovation. Of the four factors that we proposed in the model, only perceived ease of use, subjective norms, and attitude have a significant positive relationship with online purchase intention among Gen Y. The other independent variable which is perceived pricing have no significant relationship with online shopping behaviour. Therefore, retailers need to ensure that the online shopping process in their e-commerce platforms is designed to be as simple, convenient and easy as possible for Gen Y to shop online.